Reformulasi Konseptual Filsafat Islam: Kajian QS. Al-Baqarah Ayat 186 tentang Kedekatan Ilahi dan Realitas Eksistensial Manusia - Tri Yugo (UPT Publikasi Ilmiah, 2025)
This study explores Surah Al-Baqarah verse 186 through the lens of Islamic philosophy, emphasizing its ontological, epistemological, and ethical dimensions. Ontologically, the verse affirms that Allah SWT is Wājib al-Wujūd (Necessary Being), whose presence transcends space and time yet remains spiritually close to humankind. Epistemologically, it outlines that human knowledge of God arises through divine revelation and spiritual experience, especially through sincere supplication. Ethically, the verse implies that divine nearness fosters obedience, moral responsibility, and spiritual consciousness. Using a qualitative method with a thematic-interpretative approach, this paper draws from classical and modern Islamic philosophical thought. The study concludes that divine nearness (qurb Ilāhī) is not merely theological but forms a metaphysical foundation for human morality and consciousness, offering a comprehensive framework for Islamic philosophical discourse.